PJMHS 2021
DOI: 10.53350/pjmhs2115123832
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Alvarado Score in Diagnosis of Acute Appendicitis in Patients with Acute Pain Right Iliac Fossa

Abstract: Background: The gold standard treatment of acute appendicitis is appendectomy. Early surgery reduces a number of complications such as appendicular mass formation, abscess and perforation. However, diagnostic inaccuracy especially in female gender can lead to negative appendectomy because other gynecological diseases have quite similar presentation. The objective of our study is to determine the diagnostic accuracy of Alvarado scoring system in the diagnosis of acute appendicitis in comparison to the gold stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition to the great importance of correctly diagnosing patients with a high probability of appendicitis, it is also important to correctly diagnose patients with a low probability of appendicitis. Overdiagnosis of appendicitis increases the number of negative or unnecessary appendectomy cases, such that in the study by Kalan et al, 28 negative appendectomy rate were estimated to be between 20% and 40% 28–30 . In previous studies, Shuaib et al 31 and Rathod et al 32 reported 18.4% and 20.69%, respectively.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition to the great importance of correctly diagnosing patients with a high probability of appendicitis, it is also important to correctly diagnose patients with a low probability of appendicitis. Overdiagnosis of appendicitis increases the number of negative or unnecessary appendectomy cases, such that in the study by Kalan et al, 28 negative appendectomy rate were estimated to be between 20% and 40% 28–30 . In previous studies, Shuaib et al 31 and Rathod et al 32 reported 18.4% and 20.69%, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Overdiagnosis of appendicitis increases the number of negative or unnecessary appendectomy cases, such that in the study by Kalan et al, 28 negative appendectomy rate were estimated to be between 20% and 40%. [28][29][30] In previous studies, Shuaib et al 31 and Rathod et al 32 reported 18.4% and 20.69%, respectively. Several surgeons believe that raising the incidence of negative appendectomy to reduce the frequency of delay in the diagnosis of appendicitis and its related complications is admissible.…”
Section: Discussionmentioning
confidence: 98%